2021
DOI: 10.1007/s12015-021-10149-3
|View full text |Cite
|
Sign up to set email alerts
|

Induced Pluripotent Stem Cells (iPSCs) in Vascular Research: from Two- to Three-Dimensional Organoids

Abstract: Stem cell technology has been around for almost 30 years and in that time has grown into an enormous field. The stem cell technique progressed from the first successful isolation of mammalian embryonic stem cells (ESCs) in the 1990s, to the production of human induced-pluripotent stem cells (iPSCs) in the early 2000s, to finally culminate in the differentiation of pluripotent cells into highly specialized cell types, such as neurons, endothelial cells (ECs), cardiomyocytes, fibroblasts, and lung and intestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Experiments have shown that DBD decoction can promote the release of astragalus components, and the process of making freeze-dried powder may cause certain changes in the components of DBD ( Yan et al, 2010 ; Tan et al, 2021 ). Simultaneously, we will further apply vascular organoids coupled with microfluidic mass spectrometry chips to define the potential pharmacological components and deep-level molecular mechanisms of DBD on dilating blood vessels ( Wang et al, 2019 and, 2020 ; Trillhaase et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments have shown that DBD decoction can promote the release of astragalus components, and the process of making freeze-dried powder may cause certain changes in the components of DBD ( Yan et al, 2010 ; Tan et al, 2021 ). Simultaneously, we will further apply vascular organoids coupled with microfluidic mass spectrometry chips to define the potential pharmacological components and deep-level molecular mechanisms of DBD on dilating blood vessels ( Wang et al, 2019 and, 2020 ; Trillhaase et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to use iPSCs to model vascular cell types began in the late 2000s ( 93 , 94 ) resulting in a mix of several cells including VSMCs and endothelial cells (ECs), in a form of co-culture. Since then, a large number of protocols have been described using highly defined media with small molecules or cytokine cocktails to drive differentiation [several of which are well summarised in these reviews ( 95 97 )] that claim to have successfully produced VSMCs or ECs of high purities, organ-specific, developmentally pertinent lineages ( 73 , 76 ) and fine-tuned phenotypic states including the contractile one ( 37 , 98 , 99 ).…”
Section: Disease Modelling Of Tadmentioning
confidence: 99%
“…In the early stage of development, the embryonic heart is regulated by a variety of signal pathways such as Wnt, BMP, and Notch from surrounding tissues. Wnt signal is not only a key signal pathway involved in the development of cardiac mesoderm, but also an important regulatory pathway for PSC-derived cardiac lineage cells and the construction of cardiac organoids (Trillhaase et al, 2021). Therefore, when constructing cardiac organoids in vitro, it is necessary to add additional exogenous cardiogenic factors to simulate the environment for heart development in vivo (Andersen et al, 2018).…”
Section: Cardiac Organoidsmentioning
confidence: 99%